2017
DOI: 10.4172/2379-1764.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Selenium Nanoparticles from Broccoli, Characterization, Application and Toxicity

Abstract: Selenium in broccoliBroccoli belongs to the Brassicaceae family, originated in the Mediterranean regions and distributed in Europe and in the United States. Broccoli is rich in micronutrients such as carotene, vitamin C and folic acid-fibers, phytochemicals such as glucosinolates (GLs) and *Corresponding author: Kanchan Kohli, PhD, Associate Professor, Department of Pharmaceutics, Jamia Hamdard, Hamdard University, New Delhi 110062, India, Tel: +911126059688; E-mail: drkanchankohli@gmail.com AbstractPlant-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…The same group took advantage of the medicinal properties of Cassia auriculata to synthesize functional SeNPs that displayed interesting anticancer and antiproliferative characteristics [241]. Similar studies have reported the use of Vitis vinifera [32], broccoli extract [108], and Capsicum annum [242] to fabricate Se nanorods and nanoballs. Importantly, Ramamurthy et al presented a combination of SeNPs, made using fenugreek seed extract, and doxorubicin to form a chemoprotective agent against cancer [243]; Vennila et al studied the antibacterial, anticancer, and anti-inflammatory activity of SeNPs biofabricated by Spermacoce hispida and functionalized with apigenin, quinoline, quinazoline, and synaptogenin B [244]; Kokila et al reported on Se-NPs using the leaves of Diospyros montana as a biocidal agent against both Gram+ S. aureus and Gram-E. coli and the fungus A. niger [245].…”
Section: Plant-based Synthesis Of Selenium Nanoparticlesmentioning
confidence: 87%
See 3 more Smart Citations
“…The same group took advantage of the medicinal properties of Cassia auriculata to synthesize functional SeNPs that displayed interesting anticancer and antiproliferative characteristics [241]. Similar studies have reported the use of Vitis vinifera [32], broccoli extract [108], and Capsicum annum [242] to fabricate Se nanorods and nanoballs. Importantly, Ramamurthy et al presented a combination of SeNPs, made using fenugreek seed extract, and doxorubicin to form a chemoprotective agent against cancer [243]; Vennila et al studied the antibacterial, anticancer, and anti-inflammatory activity of SeNPs biofabricated by Spermacoce hispida and functionalized with apigenin, quinoline, quinazoline, and synaptogenin B [244]; Kokila et al reported on Se-NPs using the leaves of Diospyros montana as a biocidal agent against both Gram+ S. aureus and Gram-E. coli and the fungus A. niger [245].…”
Section: Plant-based Synthesis Of Selenium Nanoparticlesmentioning
confidence: 87%
“…The characterization of metalloid NPs is needed to correlate their physicochemical properties to their biological effects and toxicity [49,[104][105][106][107]. The initial physicochemical characterization of these NPs is carried out by using a myriad of routine lab techniques to analyze their shape, size and size distribution, porosity, surface chemistry, crystallinity, and dispersion pattern [108]. The most widely used techniques include UV-visible (UV-Vis) spectroscopy, luminescence spectroscopy (LS), scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM), Fourier transform infra-red spectroscopy (FT-IR), X-ray diffraction (XRD).…”
Section: Techniques Of Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants extracts act as a reservoir of several pharmacologically active metabolites and allow the synthesis of nanoparticles in well-defined size and shape controlled manner [14]. Brassica oleracea contains a wide range of biologically active compounds like glucosinolates, polyphenols, alkaloids, flavonoids and micronutrients such as vitamin C, carotene and folic acid-fibers [15]. The present work aims to investigate the role of Brassica oleracea extract in synthesis and stabilization of ZnO nanoparticles.…”
mentioning
confidence: 99%